USING OF GRAPH THEORY FOR SUMMONING FLOOD OF MEMBERS OF THE COMMISSION (Perner's Contacts, 2013)
The article deals with the coupling paths for ensuring accessibility chairmen and members of the commissions on flood alert issued by the Czech Hydrometeorological Institute and the subsequent announcement of the first degree flood flow, which cannot use the services of the mobile operator whether due to human error or loss of signal. It is used in the role of traveling salesman, exact method of solution Little algorithm and for comparing the quality of solutions heuristic by heuristic algorithm.
Keywords: TSP problem; heuristic algorithm; Little algorithm